Meta-analysis of exercise intervention on health behaviors in middle-aged and older adults - Liu, Min; Mei, Dong-hui; Zhang, Ya-lu; Kang, Ning; Wang, Dong-min; Chen, Gong (Frontiers in Psychology, 2024)
Objective To systematically review and analyze the effects of exercise interventions on health behavior among middle-aged and older adults. Methods A Meta-analysis was performed using NoteExpress software to screen randomized controlled trials (RCTs) published between January 1, 2000, and March 31, 2023, which were identified through databases including CNKI, Web of Science, Pubmed, and 6 more sources, based on predefined literature inclusion criteria. Following the quality assessment, we conducted both the overall and subgroup Meta-analyses of the exercise intervention moderator variables using Review Manager 5.4.1 software, encompassing data among the 18 RCTs. The effect size was measured as the standardized mean difference within its corresponding 95% confidence interval. Heterogeneity was assessed using the I2 metrics. Results (1) The overall results indicate a significant impact of exercise intervention on health behaviors, characterized by a large effect size [SMD = 1.02 > 0.8, 95% CI (0.73, 1.32), P < 0.001]. (2) The highest degree of heterogeneity in the relationship between exercise interventions and health behaviors was associated with the duration of one exercise session (I2= 71.2%), which was the most influential moderator variable. (3) The aerobic and resistance intervention in group exercise lasting 30–60 min per time a day, 6–7 times per week over a period of 8–12 weeks demonstrated the most substantial effect size. Conclusion (1) The exercise intervention significantly promotes the health behavior in middle-aged and older adults, emphasizing the importance of carefully considering the duration of individual exercise sessions when designing and implementing exercise intervention. (2) Considering the accessibility for middle-aged and older adults, the optimal exercise intervention should include the means of group practice, the types of aerobic and resistance exercise, with a duration of 30–60 min per time a day, beginning with a lower weekly frequency and gradually increase to 6–7 times per week, and lasting for 8 to 12 weeks. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier CRD42024506750.